Simulasi Model Matematik Difraksi Gelombang dengan Metode Elemen Hingga - Didik Purwantoro (Universitas Negeri Yogyakarta, 2007)
This paper presents results of research in mathematical model for solving mild slope equation using finite element method. In this method the model in differential equation is approximated with Galerkin smethod and then the equation formed is solved with job iteration.. The equation of refraction and diffraction can be formulated as Mild Slope equation which is assumed that the depth is constant. The result of his research indicates that mathematical model using finite element method give a good perfomance.